1992
DOI: 10.1002/bip.360320608
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures of cyclic and dicyclic analogues of growth hormone releasing factor as determined by two‐dimensional NMR and CD spectroscopies and constrained molecular dynamics

Abstract: Solution structures were determined for a linear analogue of growth hormone releasing factor (GRF), and cyclic and dicyclic analogues in which the side chains of aspartyl and lysyl residues spaced at positions i-(i + 4) were joined to form a lactam. The four analogues were [Ala15]-GRF-(1-29)-NH2 and its cyclo8-12, cyclo21-25, and dicyclo8-12;21-25 derivatives. The peptides were studied in two solvent systems: 75% methanol/25% water at pH 6.0; and 100% water at pH 3.0. CD spectroscopy was used to assess the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…The observation that 11 Ala-substituted analogues (mostly replacing hydrophilic residues) exhibited potency equal to or greater than that of the parent compound suggests that overall R-helicity and/or hydrophobicity are important factors in receptor binding. Other studies mentioned earlier [61][62][63] showed optimal lactam sizes of 20-and 21-membered rings for retention or gain in biological potencies. In contrast, we saw maximal potencies for a range of ring sizes from 18-to 20-membered [i-(i+4)] and 18-membered [i-(i+3)] lactam analogues in the C-terminus of GHRH(1-29)-NH 2 .…”
Section: Discussionmentioning
confidence: 94%
“…The observation that 11 Ala-substituted analogues (mostly replacing hydrophilic residues) exhibited potency equal to or greater than that of the parent compound suggests that overall R-helicity and/or hydrophobicity are important factors in receptor binding. Other studies mentioned earlier [61][62][63] showed optimal lactam sizes of 20-and 21-membered rings for retention or gain in biological potencies. In contrast, we saw maximal potencies for a range of ring sizes from 18-to 20-membered [i-(i+4)] and 18-membered [i-(i+3)] lactam analogues in the C-terminus of GHRH(1-29)-NH 2 .…”
Section: Discussionmentioning
confidence: 94%
“…This is the same model used in the NMR structure determination. 35 All other simulations included explicit solvent, described by a modified TIP3P water model; 36,37 the water internal geometry was constrained with the SHAKE algorithm. 38 Simulations were done with two different force fields for the protein: the CHARMM19 39 and the OPLS/AMBER 40 force fields.…”
Section: Materials and Methods Molecular Dynamics Setupmentioning
confidence: 99%
“…In all three peptides, the bridge consisted of an Asp i , Lys i+4 pair that generated a 20-membered ring. Such ring structures had been expected, from previous studies with peptide hormones and model peptides, to stabilize an α-helix [92][93][94][96][97][98][99][100]. To compare the effect of the location of the lactam bridge in a potential α-helical region for structure and bioactivity, analog A1 contained the ring structure at the C-terminal half and analog A3 at the N-terminal half of the potential α-helical region.…”
Section: Conformationally Constrained Hct Analogs To Test the Amphiphmentioning
confidence: 96%
“…In the past 25 years, the introduction of (i, i+4) side chain-to-side chain lactam bridges into potential α-helical regions has been an approach that has been successfully applied for the stabilization of the α-helical conformation in conformationally flexible polypeptide hormones including growth hormone releasing factor (GRF), neuropeptide Y (NPY), and parathyroid hormone (PTH) [1,6,[91][92][93][94][95][96][97]. According to this approach, specific residues at positions i and i+4 in the putative α-helical region are exchanged for specific diamino-and/or dicarboxylic amino acid residues, such as, for example, Lys or Orn and Asp or Glu, depending on the size of the ring structure to be generated, and the side chains of these residues are connected into a lactam bridge [91].…”
Section: Conformationally Constrained Hct Analogs To Test the Amphiphmentioning
confidence: 99%